(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
This short article arises from the need to address an issue that over time has been delayed in its analysis, but has recently become important for the growth of small businesses subsistence, mainly women, who see such activities a window to the satisfaction of their needs and monetization. In this regard, the need for comprehensive evidence to support women and role, as the foundation of the family. The training of women as being productive development within the local area, allows for socioeconomic positions that strengthen the role of women and their inclusion in production processes, both family development aimed the home. DOI: http://dx.doi.org/10.5377/reice.v2i4.1722 REICE Vol. 2, No. 4, julio-diciembre 2014: 14-19